Event-Based Ecotourism Integrated with Digital Citizen Science Framework for Blue Carbon Ecosystem Management in Indonesia (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This study examines two critical challenges in the management of blue carbon ecosystems through marine ecotourism in small island contexts: a lack of educational value and limited economic impact. We developed an integrated digital citizen science framework for Bawean Island, one of the most important blue carbon ecosystems in East Java. Daun Village in Bawean has a coastal area with 78.8 hectares of mangrove ecosystem (22 species), seagrass (7 species), and various protected marine species, including hawksbill sea turtle and dugong. FGD were designed to assess six variables: (1) current state of ecotourism, (2) local ecological knowledge and scientific understanding, (3) perceptions of educational needs, (4) preferences for ecotourism development models, (5) technology comfort levels, and (6) potential market targeting. Results are then used to design a system that aligns with local capacity, while also generating valuable information. Analysis of community perceptions shows uniformly underperformed existing attractions (1.35±0.49), low educational content (1.50±0.51), and economic impact (1.70±0.66), despite strong conservation activities (4.25±0.55). The technology comfort level shows moderate values, which results in a web-based technical system architecture using Google services. These findings indicate that Bawean Island has potential for integrating ecotourism with citizen science.